121 Factors Associated With Inflatable Penile Prosthesis Underutilization After Prostate Cancer Treatment. Issue 1 (1st April 2022) - Abdelmalek, G; Warren, C; Shen, C; Shah, T; Lulla, T; Schaefer, E; Zhou, S; Fried, D; Helemer, D; Sadeghi-Nejad, H
ABSTRACT: Introduction: Penile Prosthesis (IPP) is an effective treatment for men with ED that significantly improves quality of life but is likely being underutilized in men who were treated for prostate cancer (Pca). Objective: To better characterize the utilization of IPP treatment after Pca therapy, we explored the relationship between timing of ED diagnosis (before vs after treatment), treatment modality (radiation vs. prostatectomy), and various sociodemographic factors in a national cohort. Methods: We performed a retrospective review of SEER-Medicare patients who were diagnosed with local/regional Pca between 2006 and 2011.Using ICD9/CPT/HCPCS codes, we created a subset of patients who were diagnosed with ED 12 months prior to their Pca treatment, until 5 years after. Chi-square/Wilcoxon tests were used to detect significant differences between the use of IPP among those with ED prior to Pca treatment compared to after. In addition, various sociodemographic factors were examined. Results: Of the 31, 854 patients in our cohort, 14, 482 (45.5%) were diagnosed with ED within 12 months prior to Pca diagnosis or 5 years after diagnosis. Among those diagnosed with ED prior to treatment (4366, 30.1%), 119 (2.7%) received IPP while among the 10, 116 patients (69.9%) with ED diagnosis after treatment, 232 (2.3%) received IPP. Among patients with ED, factors decreasing the likelihood of receiving an IPP were diagnosis of ED prior to Pca treatment (OR=1.33, 95% CI: 1.06-1.66), relationship status of single (OR=1.88, 95% CI: 1.28-2.77) or divorced/separated (OR=2.13, 95% CI: 1.46-3.10), and identifying as Non-Hispanic Black (OR=1.72, 95% CI:1.24-2.37) or Hispanic (OR=1.81, 95% CI: 1.22-2.67) as compared to Non-Hispanic White men. Factors decreasing the likelihood of receiving an IPP were being treated with radiation therapy as opposed to prostatectomy (OR=0.38, 95% CI: 0.29-0.49), and increased age (OR=0.75 95% CI: 0.63-0.88). Conclusions: Although more men have their ED treated with an IPP if they received their diagnosis prior to Pca treatment (2.7% vs. 2.3%), IPPs appear to be underutilized in all patients with ED after Pca therapy. This data suggests that factors (i.e. prior ED diagnosis, being single, Black or Hispanic) outside of the typically accepted medical indications may influence IPP selection as a treatment option for ED. Conversely, counseling pertaining to IPP surgery after Pca treatment may be lacking in men with newly diagnosed ED, married men, white men, older men, and men who received radiation therapy. More thorough evaluation of these demographic factors is warranted. Disclosure: No